Relative improvements in road mobility compared to improvements in road accessibility, urbanization and economic growth - Ng, Choy Peng (2019)
Roads can be classified according to their level of mobility and accessibility. Roads with higher mobility (i.e. motorways) provide limited access but largely uninterrupted travel with high speeds, thus improving travel time reliability for transporting people and goods. Roads with higher accessibility (i.e. local roads) provide limited mobility but offer more direct routes to specific destinations, generating potential for human interactions and opportunity for socioeconomic activities. Empirical studies indicated that an increase in road length contributed positively to socioeconomic growth. However, an important missing information from previous studies remain in the literatures, which is, what type of roads (either high mobility or high accessibility roads) are needed during different level of country’s development? In order to evaluate the performance of different road types during different level of country’s development, the relative improvements in road mobility compared to improvements in road accessibility (MPA) was computed to evaluate the relationship between MPA and country’s development and the presence of trend changes. Three empirical investigations were conducted and the research objectives are as follows: (1) to evaluate how MPA facilitates export-led growth processes and to determine the investment level needed for different road types to facilitate economic and commercial activities at different developmental levels, (2) to determine the investment level required for different road types in order to facilitate urbanization at different levels of urbanization and to comprehend how the development of MPA promotes exportled urban growth and (3) to assess the indirect effect of MPA on economic growth transmitted through the impacts of MPA on urbanization and exports. To shed light on the above issues, fixed-effects panel linear regression analysis was conducted using time-series cross-sectional data on the MPA and growth data for 60 countries over the period of 31 years, from 1980 to 2010. This first empirical study divided the countries into three groups: (1) countries with a high level of development, (2) countries with a medium level of development and (3) countries with a low level of development. The key finding of this study was that a greater relative improvement in MPA would facilitate export-led growth in countries with a high and medium level of development. This indicates that policy to promote export and high mobility road network expansion should be carried out hand-in-hand to enhance economic growth. This is specifically true for countries with a medium level of development, as these countries generally suffer from lower levels of high mobility road network development. Such expansion in road mobility is necessary to fulfil demands for long-distance travel and enable the transportation of people and goods across regions, thereby facilitating productivity and trade. On the other hand, in countries with a low level of development, more investment is required to build roads with high accessibility. Such road are needed to facilitate local business and trade activities. This is crucial in order to achieve a sustainable economic growth. The second empirical study examine the effect of MPA on urbanization. The evidence presented in this study suggests that improvements in road mobility promoted exportled urban growth in countries with a low level of urbanization. This implies that policies to facilitate export should be executed in conjunction with high mobility road network expansion to increase urbanization, especially in countries with a low level of urbanization that commonly suffer from low growth rates and that have a low level of high mobility road networks. Such expansion in road mobility is required to fulfil demands for long-distance travel to transport people from rural to urban areas. In contrast, in countries with a high level of urbanization, more investment is needed to develop roads with high accessibility. Such roads are needed to fulfil daily travel demands as a consequence of urban sprawl and decentralization of employment and populations. Moreover, the evidence shows that per capita education level and physical capital stock per worker contributed to urbanization. The third empirical study examine the indirect effects MPA on economic growth, transmitted through the effects of MPA on urbanization and exports. The total effects of MPA on economic growth is computed by adding the two indirect effects. The indirect effects of MPA on economic growth were estimated based on the prediction of three different panel models: the first model relates per capita gross domestic product (GDP) with urbanization and exports, the second model associates urbanization with the MPA and the third model links exports with the MPA. The estimated results imply that the growth in MPA appeared to be associated with a rise in per capita GDP at lower level of urbanization and export but associated with a decline in per capita GDP at higher level of urbanization and export. On the other hand, for the indirect effect of MPA on per capita GDP via urbanization, the level of MPA that maximizes per capita GDP decreases with increases in the levels of physical capital stock per worker and per capita education level. For the computation of total effect, the level of MPA that maximizes per capita GDP is ranged between 0.0485 and 0.5860. In summary, this study suggest that policies focused on improving MPA should be implemented hand-in hand with other socioeconomic and urbanization policies, in order to realize a sustainable economic growth. As evidenced by empirical studies conducted in this research, high mobility road network growth alone is not sufficient to put urbanization and economy on a sustainable growth path. Although improvements in road mobility are crucial in countries with a high and medium level of development, improved road accessibility has a greater influence on export growth in countries with a low level of development. The latter can be explained as follows: at lower development levels, populations are more concentrated in smaller areas, and business activities mainly occur at the local scale. Moreover, the findings also revealed that high road accessibility has a more important impact on export growth at a high level of urbanization to support daily travel needs as a result of urban sprawl and the decentralization of employment and population. The empirical evidence indicates that the effect of relative improvements in road mobility was ambiguous, with both positive and negative effects on economic growth observed. Relative improvements in road mobility appear to be accompanied by an increase in per capita GDP at lower levels of urbanization and exports but accompanied by a decrease in per capita GDP at higher levels of urbanization and exports. Therefore, to attain sustainable economic growth, road infrastructure development policies should be implemented alongside exports and urbanization policies. In this research, most of the countries with a low level of development in the sample also had a low level of urbanization. The evidence indicates that in countries with a low level of development, improvements in high accessibility road network promote local business and trade activities. Furthermore, in countries with a low level of urbanization, improvements in high mobility road network facilitate migration from rural to urban areas. Therefore, achieving a balance road infrastructure development between both high mobility and high accessibility road network is crucial to attain sustainable economic and urbanization in countries with a low level of urbanization.